On the Take : Criminalizing Illicit Enrichment to Fight Corruption - Muzila, Lindy; Morales, Michelle; Mathias, Marianne; Berger, Tammar (Washington, DC: World Bank, 2013)
Developing countries lose an estimated US$20–40 billion each year through bribery, misappropriation of funds, and other corrupt practices. Often, the most visible manifestation of corruption is the enrichment of a corrupt public official. Despite such visibility, prosecuting corruption can be very problematic, particularly when it requires proving the offer or acceptance of a bribe. Even when the corruption is established in a court of law, linking the proceeds of the crime to the offense in order to recover assets is a complex endeavor.